Enhanced Viability and Anti-rotavirus Effect of Bifidobacterium longum and Lactobacillus plantarum in Combination With Chlorella sorokiniana in a Dairy Product - Cantú-Bernal, Servando; Domínguez-Gámez, Maribel; Medina-Peraza, Ivana; Aros-Uzarraga, Elizama; Ontiveros, Noé; Flores-Mendoza, Lilian; Gomez-Flores, Ricardo; Tamez-Guerra, Patricia; González-Ochoa, Guadalupe (Frontiers in Microbiology, 2020)
Microalgae and probiotics such as Bifidobacterium and Lactobacillus genera are associated with human beneficial effects. The aim of this study was to evaluate the activity of Chlorella sorokiniana on Bifidobacterium longum and Lactobacillus plantarum viability in a dairy product (flan) and its microbial effect against rotavirus, which is one of the major diarrhea-causing pathogens worldwide. Microalge were isolated from a Mexican river and characterized by molecular tools. Their prebiotic activity was evaluated by determining Bifidobacterium longum and Lactobacillus plantarum shelf-life after incorporation in the food matrix. In addition, HT-29 cells were infected with rotavirus Wa and treated with 1 × 109 CFU/mL L. plantarum and B. longum metabolites alone or in combination with 1 × 109 cells/mL Chlorella sorokiniana; viral titers in probiotics- and/or microalgae-treated cells were evaluated for antiviral activity. Results indicated that C. sorokiniana not only significantly (p < 0.05) improved L. plantarum and B. longum viability in flan, but also increased their antiviral activity; potent anti-rotavirus effect of C. sorokiniana alone was observed. Although more studies are needed, results suggest that incorporation of this microalga into a dairy product confers enhanced viability and antiviral effects, which indicates that C. sorokiniana might be used as an ingredient to design products with additional health benefits.